2022
DOI: 10.1093/ofid/ofac094
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and Failure Analysis of 132 Episodes of Hematogenous Periprosthetic Joint Infections—A Cohort Study

Abstract: Background Outcome of haematogenous periprosthetic joint infection (PJI) and reasons for failure are largely unknown. Methods Outcome of consecutive patients with haematogenous PJI treated at our institution between 2010 and 2019 was evaluated. Failure was classified as persistence or relapse of infection or new infection. Failure-free survival was assessed using Kaplan-Meier analysis. Proportions between groups were compared… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 29 publications
(52 reference statements)
1
17
0
8
Order By: Relevance
“…While for hematogenous infection, the clinical problem is whether the microbes detected from blood samples are causative pathogens, rather than whether the microbes could be detected. Rakow et al found that more than 61% of pathogen (43/70) causing hematogenous periprosthetic joint infection can be successfully detected from blood samples (Renz et al, 2022). For AHO, we found that the coincidence rate (sensitivity) of blood mNGS tests (77.3%) against final clinical diagnosis was slightly lower than that of puncture fluid mNGS (89.4%).…”
Section: Discussionmentioning
confidence: 53%
“…While for hematogenous infection, the clinical problem is whether the microbes detected from blood samples are causative pathogens, rather than whether the microbes could be detected. Rakow et al found that more than 61% of pathogen (43/70) causing hematogenous periprosthetic joint infection can be successfully detected from blood samples (Renz et al, 2022). For AHO, we found that the coincidence rate (sensitivity) of blood mNGS tests (77.3%) against final clinical diagnosis was slightly lower than that of puncture fluid mNGS (89.4%).…”
Section: Discussionmentioning
confidence: 53%
“…For instance, sequentially performed joint resection and implantation surgeries with existing sepsis could cause systematic inflammation response syndrome and multiple organ dysfunction syndrome. Alternatively, at least the second-stage implanted prosthesis must be removed again [ 8 ]. Moreover, the patient has to stay in bed for an additional several weeks and undergo extra surgeries.…”
Section: Introductionmentioning
confidence: 99%
“…Various competing treatment approaches have been published. The recommendations of the International Consensus Meeting (ICM) 1 , Musculoskeletal Infection Society (MSIS) 2 and Infection Disease Society of America (IDSA) 3 are mainly implemented in North America, and the concepts of the European Bone and Joint Infection Society (EBJIS) 4 and PRO-IMPLANT Foundation 5 are widely used in Europe. Despite differences in the treatment approaches, it is consent that a multidisciplinary team is crucial for successful treatment.…”
Section: Introductionmentioning
confidence: 99%
“…If the abovementioned period is exceeded, chronic infection with a mature biofilm is expected, making prosthesis exchange necessary for the eradication of infection 6 . Depending on the detected pathogen, soft tissue conditions and patientʼs compliance, revision surgery can be performed in a single- or multistage procedure 5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation